A review on influence of reactor technologies and kinetic studies for biodiesel application - Ijlal, Raheem; Mohd Nurfirdaus, Mohiddin; Tan, Yie Hua; Jibrail, Kansedo; N. M., Mubarak; Mohammad Omar, Abdullah; Mohd Lokman, Ibrahim (Elsevier B.V., 2020)
The increase in demand for energy has caused a clear contradiction between the supply and consumption of these resources, which has triggered countries to divert their attention towards biodiesel. Biodiesel yield and sustainability of the biodiesel production process are highly influenced by the catalyst. Homogeneous catalyst is the conventional method to produce biodiesel, but it requires larger water consumption to purify the final product while on the contrary heterogeneous catalyst does not require expensive utility separation cost and it can be separated from simple filtration method. Thus, this paper comprehensively reviews the conventional and advanced biodiesel reactor technologies, particularly link to the kinetic studies of different types of catalysts. The effects of the operating conditions on the reactor technology with different catalysts are discussed to observe a better oil conversion. Merits and limitations of different catalysts for biodiesel production are then compared. The kinetic studies are reviewed to compare the rate of reaction and activation energy between various types of catalysts. As the catalyst and reactor type selection affect the transesterification reaction, it is necessary to search for the correct combination of catalyst and reactor to increase the efficiency of biodiesel production at a lower cost.